1992
DOI: 10.2337/diacare.15.11.1477
|View full text |Cite
|
Sign up to set email alerts
|

Dropout and Relapse During Diabetes Care

Abstract: Dropout from treatment and relapse after temporary improvement account for a substantial amount of uncontrolled diabetes, and overcoming the obstacles of dropout and relapse has potential for significant improvement in diabetes care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 20 publications
5
78
2
Order By: Relevance
“…The data conflict with those from specialist clinics and studies of type 1 diabetes care, which have suggested that nonattenders are more likely to suffer from complications (8,9) and are more likely to smoke (9). The data do confirm the findings of Graber et al (9), who showed that nonattenders are less likely to have been prescribed medication. Subjects not receiving care had poor self-care skills, including bad dietary adherence, which correlated with less diabetes knowledge.…”
Section: Results -contrasting
confidence: 52%
“…The data conflict with those from specialist clinics and studies of type 1 diabetes care, which have suggested that nonattenders are more likely to suffer from complications (8,9) and are more likely to smoke (9). The data do confirm the findings of Graber et al (9), who showed that nonattenders are less likely to have been prescribed medication. Subjects not receiving care had poor self-care skills, including bad dietary adherence, which correlated with less diabetes knowledge.…”
Section: Results -contrasting
confidence: 52%
“…Up to 50% of adults with diabetes and somewhere between 50% and 70% of adult patients with hypertension or asthma have recurrent symptoms each year that require medical care (cf. Clark 1991; Dekker et al 1993;Graber et al 1992;Schaub et al 1993). These rates are virtually identical to what we find with addicts: somewhere between 40% and 60% of patients treated for alcohol or drug dependence return to active use within a year of some treatment intervention (cf.…”
Section: Addiction As Voluntary Behaviorsupporting
confidence: 85%
“…Less than 30% of patients with adult-onset diabetes, hypertension, or asthma observe the diet and behavioral changes required to reduce the risk factors for recurrence (cf. Clark 1991;Dekker et al 1993;Graber et al 1992).…”
Section: Addiction As Voluntary Behaviormentioning
confidence: 99%
“…The reasons for dropout from a diabetic care can be generally summarized into the following three categories: 1) patient-oriented problem (2,(11)(12)(13)(14)(15)(16)(17), 2) health-care provideroriented problem (11,18,19), and 3) physician-patient relationship (5,20). For the patient-oriented problem, gender, age, ethnicity, educational level, economical status, tobacco use, obesity, the duration of disorder, glycemic control, and psychological problems among others can be considered.…”
Section: Introductionmentioning
confidence: 99%